Adsorption of aniline by magnetic biochar with high magnetic separation efficiency. Issue 1 (1st January 2021) - Gu, Yu; Xue, Yingwen; Zhang, Dawei
ABSTRACT: The coprecipitation method was used to produce magnetic cotton straw biochar (MCS). Elemental analysis, FTIR, XRD, SEM, BET and magnetization curves were used to characterize MCS and CS. The results show that the MCS had excellent magnetic separation properties. When the pH value was higher than 5, the pH of the aniline solution had little effect on the adsorption capacity of MCS and CS. However, with increasing temperature, the adsorption capacity increased significantly. The maximum adsorption capacities of MCS and CS for aniline were 38.67 mg/g and 42.57 mg/g, respectively. The adsorption process of aniline was spontaneous, endothermic, and involved monolayer sorption and chemical adsorption. The adsorption capacity was due to the presence in magnetic biochar of phenolic hydroxyls and H-bond donors that adsorbed aniline. Therefore, the application of MCS presents good prospects for the removal of toxic and refractory aniline from water.